Comparative performance analysis of bridgeless boost and bridgeless buck converter for UPS application - Khairul Safuan Muhammad; Rahimi Baharom; Siti Zaliha M. N; Wan Noraishah Wan Abdul Munim (Institute of Advanced Engineering and Science, 2020)
In this paper, a comparative performance analysis of bridgeless boost and bridgeless buck converter for Uninterruptable Power Supply (UPS) is presented. The performance of UPS application in terms of their efficiency is compared between the conventional diode bridge converter and both bridgeless converters. The input supply power quality is also been analysed by applying open and closed loop control techniques to the converter. The results show that the efficiency and the input supply quality of the bridgeless converters are significantly improved. UPS using bridgeless boost converter has better performance in all aspect compared to bridgeless buck converter. Aligned with that, the closed loop controller for the converter has also improved the efficiency and PF more than the open loop controller in performing the UPS system. All the analytical work was performed using PSIM software.